EVALUASI KINERJA SALURAN DRAINASE PADA KAWASAN PERMUKIMAN MEKAR JAYA, DESA PEMOGAN, DENPASAR SELATAN - Ardana, Putu Doddy Heka (Jurnal Ilmiah Teknik Sipil, 2023)
Housing in Banjar Mekar Jaya, Pemogan Village with an area of 66 hectares is a densely populated area. During the rainy season, floods or inundations on Mekar Jaya always recur because it is estimated that the existing drainage system is not performing well. This study uses a quantitative descriptive approach by applying hydrological and hydraulics analysis to determine the performance of the drainage channel as well as to be able to plan the optimal dimensions of the drainage channel in Mekar Jaya housing. The results showed that there is a deviation between the existing channel discharge and the design flood discharge where the existing channel discharge is smaller than the design flood discharge and the slope of the existing channel tends to be gentle, which is around 0,0002 meters which causes the existing channel to be unable to drain rainwater or community wastewater. Based on the results of the analysis, it was found that the nine drainage channel segments in Mekar Jaya (segments A – I) have less capacity for the planned discharge that will enter the channel, namely channels A – I where the total capacity can only accommodate a flow rate of 5,480 m 3 /s while the total planned debit on channel A - I is 5,870 m 3 /s so it is necessary to make dimensional corrections along the channel. Based on the analysis of improved drainage channel dimensions, it was found that the optimal cross-section of the drainage channel on the section on Mekar Jaya is with a channel width of 3,54 meters and a channel height of 1,77 meters which can receive an outlet discharge of 5,877 m 3 /s.